Hemorrhagic Fever and Desertification Phenomenon: Demam Berdarah dan Fenomena Desertifikasi - Neamah, Dhuha Adnan; Hussein, Arwa Alaa; Sobeih, Enas Saad (Academia Open, 2024)
A collection of viral disorders known as hemorrhagic fever are brought on by various virus families and impact many bodily systems and organs, harming the cardiovascular system overall. The symptoms can include circulatory instability, coagulation problems, altered mental state, and, in extreme cases, death. Desertification is the process by which land in arid, semi-arid, and dry regions deteriorates due to a lack of water sources, causing a decline in biodiversity and plant life, which in turn causes the topsoil layer to disappear and, ultimately, the land’s capacity to sustain human, animal, and agricultural life. Highlights: Hemorrhagic fever: viral disorders harming organs, cardiovascular system, causing death. Symptoms: circulatory instability, coagulation issues, altered mental state, fatal outcomes. Desertification: land degradation reduces biodiversity, plant life, and agricultural capacity. Keywords: Hemorrhagic fever , Desertification, Viral Hemorrhagic Fever (VHF)